2013
DOI: 10.1159/000351466
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Body Composition and Resting Energy Expenditure in Childhood in Preterm Children Born with Very Low Birth Weight

Abstract: Background: Rapid early ponderal growth is associated with adverse metabolic risks in young adults born at term. Aim: To determine whether there are differences in body composition, resting energy expenditure (REE) and metabolic variables between preterm children born with very low birth weight (VLBW) either appropriate (AGA) or small (SGA) for gestational age and whether these differences are related to an early period of weight gain. Methods: 67 VLBW preterm (40 AGA, 27 SGA). Body composition by DEXA, REE by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 20 publications
3
25
1
Order By: Relevance
“…In line with previous studies [23,24,25], the present study showed that, in preterm infants, higher weight gain during the first 6 months after term age resulted in higher FM and higher leptin at 6 months' CA. In contrast with Hernandez et al [26], weight gain during the first 6 months after term age was positively associated with FM and leptin in both SGA and AGA preterm infants.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies [23,24,25], the present study showed that, in preterm infants, higher weight gain during the first 6 months after term age resulted in higher FM and higher leptin at 6 months' CA. In contrast with Hernandez et al [26], weight gain during the first 6 months after term age was positively associated with FM and leptin in both SGA and AGA preterm infants.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with these findings, Sepulveda et al (25) found a positive association between weight gain in the first 3 months of life and total fat in 67 preterm children born with very low birthweights and assessed at 6 years of age using dual-energy X-ray absorptiometry. On the contrary, we did not find any correlation between delta weight gain at an equivalent term age of 6 months and body composition parameters.…”
Section: Discussionmentioning
confidence: 64%
“…Rapid weight gain in early infancy increases future cardiometabolic risk [1,2,3,4] and predicts obesity in later childhood [5,6], adolescence and adulthood [7,8]. There is also evidence that the metabolic consequences of obesity can begin in childhood, as it is associated with increased inflammatory markers [9], immune dysregulation [10] and hypertension [11,12] from an early age.…”
Section: Introductionmentioning
confidence: 99%